Enhance Urisdictions on the Implementation of Uncertain Time Working Agreements - Muhammad Mahendra M. Sinaga (Budapest International Research and Critics University, 2022)
An Indefinite Time Work Agreement is an unspecified work agreement, which is permanent and valid forever until termination of employment. This type of research uses empirical juridical research using qualitative data using purposive sampling in taking samples. The research method used is field research. The data collection technique used is through interviews and literature as well as other sources that support and relate to this research.